Design of a polygeneration system with optimal management for a dhc network - Lazzeroni, Paolo (International Journal of Sustainable Energy Planning and Management, 2019)
Nowadays, District Heating and Cooling (DHC) networks represent a viable and efficient way to distribute energy for space heating and cooling in urban areas with high density demand. This is particularly true in a context characterized by higher fuel price and restrictive regulatory framework. DHC systems give the possibility to integrate energy sources available in the territory and supply thermal energy vector to a conveniently large number of end-users; these are thus potentially capable to cover the demand at lower costs, higher efficiency and reduced emissions compared to not centralized systems. In Europe, the Directive 2012/27/EU pointed out the need for these systems, introducing the definition of ‘efficient DHC’: at least 50% of renewable energy, 50% of waste heat, 75% of cogenerated heat or 50% of a combination of such energy and heat should be used. This paper presents the design assessment of the generation facilities for an existing DHC network located in the northern part of Italy. The design stage considers boiler, Combined Heat and Power (CHP), solar thermal, absorption/electric chiller and other low enthalpy sources as options of the case study. The sizes of the generation units are defined according to the heating/cooling demand of the buildings supplied by the DHC, the estimated network losses and the present regulatory framework. The plant management is identified through an optimization procedure capable to minimize the operational costs according to the technical characteristics and constraints of the plant. Four different configurations with increasing costs saving, installation costs, Renewable Energy Sources (RES) generation and Primary Energy Saving (PES) are presented. A preliminary economic evaluation is also presented for the various configurations considering the Italian incentive schemes. Finally, an energy assessment is presented to highlight the share of the different sources in each configuration and to evaluate their compliance to the EU Directive on efficient DHC .